2021
DOI: 10.4254/wjh.v13.i2.218
|View full text |Cite
|
Sign up to set email alerts
|

Production and activity of matrix metalloproteinases during liver fibrosis progression of chronic hepatitis C patients

Abstract: BACKGROUND Matrix metalloproteinases (MMPs) participate in the degradation of extracellular matrix compounds, maintaining the homeostasis between fibrogenesis and fibrolytic processes in the liver. However, there are few studies on the regulation of liver MMPs in fibrosis progression in humans. AIM To assess the production activity and regulation of matrix metalloproteinases in liver fibrosis stages in chronic hepatitis C (CHC). METHODS A pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
8
0
7
Order By: Relevance
“…Thus, we evaluated OC ability in affecting MMP mRNA expression in LX2 cells, observing that MMP2, 3 and 7 were significantly reduced by OC treatment, whereas only a decreasing tendency could be observed for MMP9, probably due to the high variability observed in the experiments. These results are in line with experimental and clinical observations, demonstrating the intriguing interplay between MMPs and collagen deposition, and reporting increased hepatic and plasmatic concentrations of some MMPs (in particular, MMP2, 7 and 9) in liver fibrosis ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we evaluated OC ability in affecting MMP mRNA expression in LX2 cells, observing that MMP2, 3 and 7 were significantly reduced by OC treatment, whereas only a decreasing tendency could be observed for MMP9, probably due to the high variability observed in the experiments. These results are in line with experimental and clinical observations, demonstrating the intriguing interplay between MMPs and collagen deposition, and reporting increased hepatic and plasmatic concentrations of some MMPs (in particular, MMP2, 7 and 9) in liver fibrosis ( 36 , 37 ).…”
Section: Discussionsupporting
confidence: 90%
“…A recent study reported that serum concentrations of MMPs are increased in chronic HCV infection, but gelatinases are inactive during fibrosis progression. When the collagenolytic activity was evaluated, lower values were found in METAVIR stages F2, F3, and F4 compared to stage F1 [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA and protein expression of several MMPs is modified during chronic hepatitis C: the gelatinases MMP-2 and -9 are enhanced [ 57 , 58 , 76 ], while the collagenases MMP-1 and -13 are downregulated [ 57 ]. A recent study reported increased serum levels of MMP-2, -7, and -9 in patients with chronic hepatitis C, which correlated to the fibrosis stage for MMP-7 [ 90 ]. Gelatinases contribute to the degradation of the basement membrane collagen IV, while collagenases such as MMP-1 and -13 break down interstitial collagens I and III.…”
Section: Liver Fibrosis and Cirrhosismentioning
confidence: 99%